Building a multi-media scale for security education in sports stadiums from the point of view of those in charge of managing the security of football stadiums - Fahad, Saad; Al-Fatlawi , Hamid (Journal of Physical Education, 2025)
The research aims to build a scale (multiplicity of sports media) from the point of view of those in charge of managing the security of Iraqi football stadiums and to identify the role of the multiplicity of sports media in security education for sports stadiums, using the descriptive research methodology in the survey method, on the research sample represented by those in charge of managing the security of sports stadiums in football working in (the Iraqi Ministry of Interior, the Ministry of Youth and Sports and the Iraqi National Olympic Committee), which amounted to (592) divided into three exploratory samples (10), structural (300), and the main Applied (282), the researcher used the system (SPSS) to process the research data statistically, to find out the validity of the construction of the scale, and after the results obtained by the researcher reached that the scale (multiplicity of sports media) contributes to the contribution rate (58.6%) to security education in sports stadiums, although the scale is suitable for what was built for it according to the conditions of measurement and construction in the science of sports management, and the researcher recommended the need for coordination between those in charge of managing the security of sports stadiums with multiple sports media to support and spread security education In stadiums, with the establishment of seminars, conferences and workshops with the participation of researchers and academics and the presence of federations, clubs and heads of fan associations with the aim of security education in football sports stadiums.